2018
DOI: 10.1111/echo.14217
|View full text |Cite
|
Sign up to set email alerts
|

Presystolic wave is associated with carotid intima media thickness

Abstract: Introduction Carotid intima media thickness (CIMT), a direct marker of atherosclerosis, has emerged as a promising means for cardiovascular risk evaluation. Presystolic wave (PSW) is commonly detected by the Doppler interrogation of the left ventricular outflow tract (LVOT). It is thought to be a result of a stiff left ventricle and impaired LV compliance. Herein, we aimed to investigate a possible association between carotid intima media thickness, an atherosclerotic marker, and PSW. Method We prospectively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The main drawbacks of echocardiography in IHD patients include being operator dependent and the variability in cardiac echogenicity 10 . One of the indices in the Doppler assessment of the left ventricular outflow tract is the presystolic wave (PSW) 11 . The exact mechanism of the PSW is not yet known, but it is hypothesized that the PSW is mainly due to the left ventricular stiffness and also, is a marker of impaired LV compliance 11 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main drawbacks of echocardiography in IHD patients include being operator dependent and the variability in cardiac echogenicity 10 . One of the indices in the Doppler assessment of the left ventricular outflow tract is the presystolic wave (PSW) 11 . The exact mechanism of the PSW is not yet known, but it is hypothesized that the PSW is mainly due to the left ventricular stiffness and also, is a marker of impaired LV compliance 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism of the PSW is not yet known, but it is hypothesized that the PSW is mainly due to the left ventricular stiffness and also, is a marker of impaired LV compliance 11 . Presence and velocity of the PSW are related to the carotid‐ intima media thickness that is a useful factor for assessment of subclinical atherosclerosis 11 . It was also shown, the absence of PSW in asymptomatic patients was related to the increased risk for cardiovascular disease 12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Presystolic wave (PSW) is an image which is frequently, albeit not necessarily, observed on the outflow tract of the left ventricle (LVOT) later in the diastolic period upon Doppler echocardiographic imaging (13,14). Although PSW's exact prevalence and clinical importance in diverse medical conditions are not well recognized, preliminary evidence suggested that its absence could indicate adverse CV events in patients with overt left ventricular (LV) failure (14,15), subclinical LV dysfunction in asymptomatic HT patients (16), higher Syntax score in patients with acute myocardial infarction (15), worsening arterial elasticity in asymptomatic subjects (13), and increased carotid plaque burden in patients with multiple CV comorbidities (17). Not only its absence, but its velocity was also proposed to have clinical implications (13,14,16,17).…”
Section: Introductionmentioning
confidence: 99%